The role of social networks in the building of physical activity trails in the state of Kansas - Lightner, Joseph S. (Kansas State University, 2013)
Background and Purpose: Trails can help increase community physical activity levels but little is known about the role that collaborations play in building a trail. Social network analysis may be a useful tool to examine collaborations among various stakeholders, such as municipal public works, parks and recreation, community organizations, hospitals, local businesses, universities, and schools. The purpose of this project is threefold: a) to identify the number and type of organizations involved in trail building, b) to examine the centrality and density of social networks in the trail building process and c) to determine whether collaborations differ between the three phases of trail building (generation, grant funding and construction). Methods: Thirty-four successful trail project builders funded by the Sunflower Foundation of Kansas participated in an online survey designed to explore collaborations throughout the trail building process. Social network analysis adapted from procedures developed by Wickizer and colleagues (1993) was used to identify key organizations in building trails, to estimate the overall density and centrality of connections between the organizations, and to determine differences in collaborations by project phase. Results: Fifteen different groups (e.g. non-profit community organizations, city parks and recreation department, city public works, schools) were identified as part of the trail building process. Non-profit community organizations were most central to trail building during all three phases (generation (.36) grant writing (.38), and construction (.41)). All three phases of trail building were only weakly connected as indicated by density of social network scores measured during the generation (5.7%), grant writing (6.2%) and construction phases (7.5%). Centrality of social networks was high for all three phases of the trail building process, the generation phase (0.32) the grant writing phase (0.27) and the construction phase (0.36). Conclusions: This exploratory analysis suggests Social Network Analysis may be a useful tool to study organizations that collaborate to build trails for physical activity. During the distinct phases of trail-building, the role of collaborations changed. Some organizations were more important in the planning phase, grant writing or construction, while others (e.g. non-profit community organizations) were important throughout the entire process. Additionally, the density of social network increased as the trail projects progressed. The relationships between organizations were often weak but provided a flow of necessary information and skills to successfully build a trail. Future research should attempt to understand these time-dependent collaborations and encourage them in future trail and other built environment projects that support physical activity.
Keywords: Physical activity; Trails; Social network analysis; Community health; Kinesiology (0575)